PENINGKATAN KEMAMPUAN MOTORIK ANAK DENGAN KEGIATAN MERONCE TK MUSLIMAT NU III KEC. PANGARENGAN KAB. SAMPANG - Norani Norani (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to improve children's fine motor skills through group B monitoring activities in kindergarten. The research design refers to the motion research of the lecture hall, especially planning, standing, seeing, and reflecting. The source of the recordings for this study were 20 students at institution B. The information series strategy on this test was accomplished using a) statements, namely checklists, anecdotal notes, and works; b) Documentation. Information evaluation approach is achieved through descriptive qualitative. The results of this study indicated that the activities carried out through meronce showed an increase from cycle 1 to cycle 2, the average fine motor skills of children became 7.15 with a percentage of 35.75%. Based on this, through meronce activities in group B children in kindergarten can improve children's motoric quality. Keywords: Motoric, Meronce